The Influence of Customer Relationship Management Activities and Service Quality on Customer Satisfaction in Jagakarsa Health Center and Setiabudi Health Center - Farah Saufika; MGS. Aritonang; Henky Lesmana (Humanistic Network for Science and Technology (HNST), 2018)
This research was conducted to know the activity of Customer Relationship Management (CRM) and services quality that affect customer satisfaction in Jagakarsa health center and Setiabudi health center. Questionnaires with closed question designs were used as research instruments, and as many as 190 respondents were sampled in the study. Data analysis technique that used was quantitative descriptive method, SPSS 20 for windows program used to analyze obtained data after the research. This research showed that the activity of CRM and service quality influence customer satisfaction in Jagakarsa health center and Setiabudi health center. Partially, the significance value was 0.000, which means the model was accepted, it means the activity of CRM significantly affected the customer satisfaction. From different test that there was no significant difference of activity of CRM and service quality to customer satisfaction at Jagakarsa health center and Setiabudi health center and there was no significant difference between influence of CRM activity and service quality to patient satisfaction of BPJS and general in Jagakarsa health center and there was a significant difference from the influence of CRM activity and service quality to customer satisfaction in BPJS and general patient at Setiabudi health center. Keywords: Customer Relationship Management, Service quality, Customer satisfaction, Health center